A systematic review of policy and clinical guidelines on positive risk management. (2nd January 2023) - Just, Daniela; Tai, Sara; Palmier-Claus, Jasper
Abstract: Background: National policies and guidelines advocate that mental health practitioners employ positive risk management in clinical practice. However, there is currently a lack of clear guidance and definitions around this technique. Policy reviews can clarify complex issues by qualitatively synthesising common themes in the literature. Aims: To review and thematically analyse national policy and guidelines on positive risk management to understand how it is conceptualised and defined. Method: The authors completed a systematic review (PROSPERO: CRD42019122322) of grey literature databases (NICE, NHS England, UK Government) to identify policies and guidelines published between 1980 and April 2019. They analysed the results using thematic analysis. Results: The authors screened 4999 documents, identifying 7 eligible policies and 19 guidelines. Qualitative synthesis resulted in three main themes: i) the conflicting aims of positive risk management ; ii) conditional positive risk management ; and iii) responsible positive risk management . Conclusions: Analysis highlighted discrepancies and tensions in the conceptualisation of positive risk management both within and between policies. Documents described positive risk management in different and contradictory terms, making it challenging to identify what it is, when it should be employed, and by whom. Five policies offered only very limited definitions of positive risk management.